2022
DOI: 10.3390/plants11020214
|View full text |Cite
|
Sign up to set email alerts
|

QTL Mapping Low-Temperature Germination Ability in the Maize IBM Syn10 DH Population

Abstract: Chilling injury poses a serious threat to seed emergence of spring-sowing maize in China, which has become one of the main climatic limiting factors affecting maize production in China. It is of great significance to mine the key genes controlling low-temperature tolerance during seed germination and study their functions for breeding new maize varieties with strong low-temperature tolerance during germination. In this study, 176 lines of the intermated B73 × Mo17 (IBM) Syn10 doubled haploid (DH) population, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
(69 reference statements)
0
10
0
Order By: Relevance
“…In general, seed germination speed reduces when germination temperature decreases. For maize, it was reported that the minimum temperature for germination is 10 °C [ 33 ], and it was commonly set as 10 °C for the low temperature germination treatment [ 31 , 34 , 35 ]. We previously used this experimental condition to conduct QTL mapping in an F 2:3 population crossed from L220 and PH4CV and identify a major QTL, qp1ER1-1, for maize LTGA [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, seed germination speed reduces when germination temperature decreases. For maize, it was reported that the minimum temperature for germination is 10 °C [ 33 ], and it was commonly set as 10 °C for the low temperature germination treatment [ 31 , 34 , 35 ]. We previously used this experimental condition to conduct QTL mapping in an F 2:3 population crossed from L220 and PH4CV and identify a major QTL, qp1ER1-1, for maize LTGA [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Seed harvested from L220, PH4CV, and NILs were used for LTGA evaluation according to the methods described by Li et al (2018) and Zhang et al (2020) [ 31 , 35 ]. For emergence rate testing, 30 seeds were surface sterilized for 5 min in 0.1% sodium hypochlorite and rinsed three times with distilled water, then sown in sterile sand with moisture content of 16% in a plastic box, which incubated in a dark chamber at 10 °C ER was defined as shoots breaking through the sand and counted from 17 to 25 days after sowing (DAS) with a 2-day interval.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies into FT mainly focused on QTL mapping in alfalfa (in genomics level) ( Adhikari et al, 2019 ; Zhang et al, 2020 ). Although integration of QTL mapping and RNA-seq has been applied to identify candidate genes in rice, maize ( Zea mays L.), wheat ( Triticum aestivum L.), and other crops ( Kuang et al, 2020 ; Lei et al, 2020 ; Han et al, 2022 ), but such approaches have not been used for discovering alfalfa FT genes. In this study, flower samples at three flowering stages from two parents of the F 1 mapping population were characterized using the RNA-seq technology, and the identified DEGs were combined with QTLs to narrow the candidates.…”
Section: Discussionmentioning
confidence: 99%
“…The genes with putative function related to auxin and gibberellin response were identified in the QTL region. Recently, Han et al (2022) mapped five QTL clusters on chromosomes 1, 2, 3, 4, and 9 using an B73 x Mo17 (IBM) Syn10 double haploid population. From these clusters, 39 genes were extracted, and through RNA-seq, upregulated genes from B73 and Mo17 were identified.…”
Section: Role Of Micro Rnas In Abiotic Stress Tolerance In Maizementioning
confidence: 99%